Evaluating approaches to resource management in consumer product sectors - An overview of global practices. (1st July 2019) - Singh, Jagdeep; Cooper, Tim; Cole, Christine; Gnanapragasam, Alex; Shapley, Matthew
Abstract: Addressing global sustainability challenges associated with natural resource security and climate change requires new perspective on waste and resource management. Sustainability-driven business model innovations have a crucial role in transforming current, unsustainable, production and consumption patterns by slowing product replacement and closing material cycles. This study identifies best practice across a range of consumer product sectors. The study developed a novel methodology to identify and evaluate practical approaches to resource efficiency and the circular economy in order to reduce energy and material demand in these product sectors. These approaches include durable product design, enhanced repair and upgrade services, and product take-back. The study analysed 519 products and identified a total 145 examples of best practice within their respective product sectors that provide important insights into planning more circular business models in a range of product sectors. The paper highlights major barriers to, and opportunities, for wider implementation of these practices. Highlights: Products were evaluated based on practical approaches to prolong product lifetimes and close material cycles An overview of current best practices was presented based on the evaluation of 519 consumer products Study identified 145 examples of the current 'best practice' that could lead sustainable innovations in the studied sectors Studied identified a huge gap in current business models that do not focus on value recovery from post-consumer discards Major barriers and opportunities to the best practices for a wider implementation were highlighted.